The impact of state laws on motor vehicle fatality rates, 1999–2015. Issue 6 (June 2020) - Notrica, David M.; Sayrs, Lois W.; Krishna, Nidhi; Rowe, Dorothy; Jaroszewski, Dawn E.; McMahon, Lisa E.
Abstract : BACKGROUND: Motor vehicle crash (MVC) fatalities have been declining while states passed various legislation targeting driver behaviors. This study assesses the impact of state laws on MVC fatality rates to determine which laws were effective. METHODS: Publically available data were collected on driver-related motor vehicle laws, law strengths, enactment years, and numbers of verified-trauma centers. Prospective data on crash characteristics and MVC fatalities 16 years or older from Fatality Analysis Reporting System 1999 to 2015 (n = 850) were obtained. Generalize Linear Autoregressive Modeling was used to assess the relative contribution of state laws to the crude MVC fatality rate while controlling for other factors. RESULTS: Lowering the minimum blood alcohol content (BAC) was associated with largest declines for all ages, especially the older cohorts: 16 years to 20 years ( B = 0.23; p < 0.001), 21 years to 55 years ( B = 1.7; p < 0.001); 56 years to 65 years ( B = 3.2; p < 0.001); older than 65 years ( B = 4.1; p < 0.001). Other driving under the influence laws were also significant. Per se BAC laws accompanying a reduced BAC further contributed to declines in crude fatality rates: 21 years to 55 years (B = −0.13; p < 0.001); older than 65 years ( B = −0.17; p < 0.05). Driving under the influence laws enhancing the penalties, making revocation automatic, or targeting social hosts had mixed effects by age. Increased enforcement, mandatory education, vehicle impoundment, interlock devices, and underage alcohol laws showed no association with declining mortality rates. Red light camera and seatbelt laws were associated with declines in mortality rates for all ages except for older than 65 years cohort, but speed camera laws had no effect. Graduated Driver License laws were associated with declines for 16 years to 21 years ( B = −0.06; p < 0.001) only. Laws targeting specific risks (elderly, motorcycles, marijuana) showed no effect on declining MVC mortality rates during the study period. CONCLUSION: States have passed a wide variety of laws with varying effectiveness. A few key laws, specifically laws lowering allowable BAC, implementing red light cameras, and mandating seatbelt use significantly reduced MVC mortality rates from 1999 to 2015. Simply adding more laws/penalties may not equate directly to lives saved. Continued research on state laws will better inform policy makers to meet evolving public health needs in the management of MVC fatalities. LEVEL OF EVIDENCE: Epidemiological, Level III. Abstract : Supplemental digital content is available in the text.